2015
DOI: 10.1007/s11771-015-2541-7
|View full text |Cite
|
Sign up to set email alerts
|

DMAc used as a reducer for preparation of spherical silver nanoparticles with high dispersion

Abstract: A silver nanoparticle (AgNP) with good monodispersity was produced by a convenient method for reducing of AgNO 3 with N, N-dimethylacetamide in the presence of polyvinyl pyrrolidone (PVP) as the surface modification agent. The shape and size of the AgNP with reaction time were taken as variables. The surface plasmon band transition was monitored with reaction mixture time at different temperatures. The AgNP crystallinity increases with the reaction time, and the reduction efficiency is very low when AgNP solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In exploring the capability of amide‐based organic compounds as reductants, some studies have reported the use of N , N ‐dimethylacetamide (DMAc) in the synthesis of highly dispersed Ag spheroidal nanocrystals in a surfactant‐free system, in which DMAc served as a solvent, and a stabilizer, in addition to a reductant . However, in contrast to DMF, the exact mechanism involved in the oxidation of DMAc is yet to be explored.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In exploring the capability of amide‐based organic compounds as reductants, some studies have reported the use of N , N ‐dimethylacetamide (DMAc) in the synthesis of highly dispersed Ag spheroidal nanocrystals in a surfactant‐free system, in which DMAc served as a solvent, and a stabilizer, in addition to a reductant . However, in contrast to DMF, the exact mechanism involved in the oxidation of DMAc is yet to be explored.…”
Section: Case Studiesmentioning
confidence: 99%
“…Moreover, the reductant, depending on the physicochemical properties and experimental conditions, may directly affect the outcome of a synthesis due to its major impact on the reaction kinetics and thus the nucleation and growth of nanocrystals. To this end, many studies have recently started to systematically evaluate different types of reductants in an effort to elucidate the correlations between their properties and the final shape/morphology of the nanocrystals . Figure summaries a series of compounds that have been employed as reductants for the colloidal synthesis of metal nanocrystals through chemical reduction, differentiated by a large number of distinctive functional groups such as hydroxyl, carbonyl, and benzene, among others.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the interface area and metal Materials 2023, 16, 5505 2 of 10 dispersion, much work had been completed recently [20,21]. The synergistic antibacterial activity of silver with cerium oxide composites was also discussed [20][21][22][23][24]. Li et al [20] reported that a Ag/CeO 2 nanocomposite prepared via selective laser welding in liquid had obvious composite interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Ag NPs can be reduced from Ag + by chemical reduction with several reducing agents such as sodium borohydride (NaBH 4 ), sodium citrate, N,N‐Dimethylformamide, N,N‐dimethylacetamide, aniline, ubiquitous natural organic matters . Among these reducing agents, NaBH 4 is widely used.…”
Section: Introductionmentioning
confidence: 99%